2015
DOI: 10.1371/journal.pntd.0003626
|View full text |Cite
|
Sign up to set email alerts
|

High Seroprevalence for Spotted Fever Group Rickettsiae, Is Associated with Higher Temperatures and Rural Environment in Mbeya Region, Southwestern Tanzania

Abstract: BackgroundRickettsioses are endemic in sub-Sahara Africa. Burden of disease, risk factors and transmission are hitherto sparsely described.MethodsFrom the EMINI (Evaluating and Monitoring the Impact of New Interventions) population cohort, we randomly selected 1,228 persons above the age of 5 years from the nine participating communities in Mbeya region, Southwestern Tanzania, stratified by age, altitude of residence and ownership of domestic mammals, to conduct a cross-sectional seroprevalence study in. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 27 publications
4
12
0
Order By: Relevance
“…Together with previous reports on RVFV, rickettsiae of the typhus group and spotted fever group, we are demonstrating comparably high seroprevalences which could be caused by considerable exposure of the population to arthropod-borne infections other than malaria [23], [26], [27]. Akin to RVFV, a near-linear correlation of anti- Alphavirus IgG prevalence with age suggests endemic exposure rather than single or few epidemic events.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Together with previous reports on RVFV, rickettsiae of the typhus group and spotted fever group, we are demonstrating comparably high seroprevalences which could be caused by considerable exposure of the population to arthropod-borne infections other than malaria [23], [26], [27]. Akin to RVFV, a near-linear correlation of anti- Alphavirus IgG prevalence with age suggests endemic exposure rather than single or few epidemic events.…”
Section: Discussionsupporting
confidence: 79%
“…Rural living conditions, defined by low population density and long distances to roads, was a risk factor in our analysis of SFG rickettsia IgG [27]. Others authors also found this to be a risk factor for anti- Alphavirus IgG [33], so it is possible that rural conditions are the factor which increases the risk for both of these diseases which do not have much else in common.…”
Section: Discussionmentioning
confidence: 64%
“…7 The indigenous community in Malaysia (also referred as Orang Asli or ‘original people') constitutes a minority group (0.6%) of the total population in Malaysia. 8 They stay in huts or settlements that are surrounded by primary or secondary forest, and engage in activities involving agriculture, hunting and collection of forest products.…”
Section: Introductionmentioning
confidence: 99%
“…People who live at the fringe of the forest or rural areas, including the indigenous community and animal farm workers, are regarded as populations who are at high risk of acquiring rickettsioses. 7 The indigenous community in Malaysia (also referred as Orang Asli or ‘original people') constitutes a minority group (0.6%) of the total population in Malaysia. 8 They stay in huts or settlements that are surrounded by primary or secondary forest, and engage in activities involving agriculture, hunting and collection of forest products.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Recent etiologic investigations of febrile illness in Tanzania have detected the prevalence of a variety of pathogens, including zoonoses, such as leptospirosis, brucellosis, salmonellosis, and Q-fever, and vector-borne pathogens, such as dengue virus, chikungunya virus, and Rift Valley fever virus. [9][10][11][12][13][14][15][16][17][18] In Tanzania's Morogoro region, diseases such as acute respiratory infections (ARIs), urinary tract infections, and typhoid fever have also recently been reported. [19][20][21] These agents may contribute to high morbidity and mortality in humans, and therefore, awareness of such acute febrile illness (AFI)-associated agents should be more fully evaluated among at-risk communities.…”
Section: Introductionmentioning
confidence: 99%